P34 Using an evidence base to include simulation training in physician curricula. (3rd November 2019) - Armstrong, Miriam; Purva, Makani; Jones, Mike; Black, David
Abstract : Introduction: In 2014 a literature review was undertaken on behalf of the Expert Group on Simulation in Core Medical Training (CMT), hosted by the Joint Royal Colleges of Physicians Training Board (JRCPTB) and Health Education England (HEE), to evaluate the use of simulation-based education (SBE) in CMT. The review aimed to identify where SBE might be utilised to improve the quality of CMT and to make recommendations for implementation. Methods: Searches were conducted in MEDLINE (English language texts published from 1996–2015 inclusive) to identify SBE evidence applicable to the 2009 CMT curriculum. Concurrently an online survey of UK-wide CMT training programme directors was conducted by Dundee University to assess current and potential future practice. Summary of results: Evidence supporting training using SBE in CMT was found in 90 individual studies. The main findings were: There is good evidence that certain CMT practical procedures (central venous catheterisation, thoracentesis, abdominal paracentesis) and emergency presentations (cardiorespiratory arrest) improve patient safety if taught by SBE. There is no reason why additional CMT procedures should not also be taught using SBE, indeed evidence suggests this is desirable. There is reasonable evidence that non–technical and human factors CMT skills can be effectively taught using SBE. That the teaching of CMT procedures and non–technical skills using SBE is already widespread within the UK and training programme directors support its use. Discussion, conclusions and recommendations: Based on these findings the JRCPTB recommended the following to the General Medical Council in 2017: That all essential and desirable practical procedures listed in the CMT curriculum should be taught by simulation as early as possible in Year One, with further simulation teaching, involving human factors and scenarios training, carried out in either Year One or Year Two. The latter should also include refresher training for procedural skills, where necessary. These recommendations have now been incorporated into the Internal Medicine curriculum being implemented from August 2019 and will be considered for inclusion into higher specialties. References: Joint Royal College of Physicians Training Board & Health Education England. Enhancing UK Core Medical Training through simulation-based education: an evidence-based approach. A report from the joint JRCPTB/HEE Expert Group on Simulation in Core Medical Training. 2016. https://www.jrcptb.org.uk/news/enhancing-uk-core-medical-training-through-simulation-based-education-sbe-evidence-based [Accessed 3 June 2019].